Application of motion capture technology based on wearable motion sensor devices in dance body motion recognition - Li Qianwen (Measurement: Sensors, 2024)
In recent years, people have been committed to studying how to recognize human behavior through the use of wearable devices and understand the intentions expressed by human actions, which has also attracted much attention in human-computer interaction. At present, research on dance mainly relies on computer simulation, while wearable devices can more realistically reflect the details and dynamic processes of dance movements. In order to realize the recognition of dancing human movements, this paper proposes a system that combines Motion capture technology and wearable devices, and uses wearable devices for recognition. Before the experiment began, we established a process for collecting and preprocessing dance action data. On the basis of in-depth research and analysis of Motion capture technology, we have successfully constructed a human Motion capture data-driven system, which can obtain the data needed by the human body to dance through wearable devices. After experimental verification, the system designed in this article performs excellently in recognizing human movements in dance. The recognition results not only contribute to dance training and correcting errors, but also gradually become an important way for dance learning, providing new ideas for dance learning and inheritance.